Adopting marketing intelligence to achieve competitive advantage: Applied research in a sample of the union bank of Iraq - Ammar Salih, Aya; Ali Jassim, Tarik (Edelweiss Applied Science and Technology, 2024)
The purpose of this research is to investigate how a marketing intelligence system may help an organization get a competitive edge within the study setting and to comprehend the practicalities of doing so. There were two variables in the study: marketing intelligence, which was represented by the dimensions of customer understanding, market analysis, product intelligence, and competitor monitoring, was the independent variable, and competitive advantage, which was represented by the dimensions of cost, quality, flexibility, and delivery, was the dependent variable. Surveys were used in the study to get firsthand information from the Union Bank of Iraq in the province of Baghdad. A deliberate sample including thirty bank managers was chosen. SPSS V.26 software was utilized to process the data utilizing a range of statistical methods. The investigation produced a number of findings. The most notable of them was the direct connection and beneficial impact of the marketing intelligence system on Union Bank of Iraq's ability to gain a competitive edge. A number of recommendations were also made, the most notable of which being that the management of the bank should monitor environmental changes in order to recognize changes in the market, take advantage of opportunities, and address dangers.